Effect of changes in cerebral blood flow on proportion of high and low flow tissue in the brain. Issue 6 (June 1974) - Iliff, Linnette; Zilkha, E.; Bull, J. W. D.; Boulay, G. H. Du; McAllister, V. L.; Marshall, John; Russell, R. W. Ross; Symon, Lindsay
Abstract : Regional cerebral blood flow was measured by injection of 133 Xenon into the internal carotid artery in 11 patients with cerebrovascular disease. All patients were studied under general anaesthesia, first at normocapnia and then at hypocapnia. The 15 minute isotope clearance curves were analysed by computer by two-compartmental analysis and regional changes in flow and the proportions of fast and slow clearing tissue obtained at two levels of arterial CO2 tension. Hypocapnia caused a fall in blood flow which was consistently accompanied by a decrease in the proportion of fast clearing tissue. Regional changes were not significantly different from the hemisphere mean changes. There was no correlation between changes in blood flow through grey matter and the proportion of fast clearing tissue on a hemisphere mean basis, but on regional analysis the data from 10 out of the 11 patients showed that in areas where blood flow through grey matter changed most the proportion of fast clearing tissue changed least and vice versa . A hypothesis has been proposed to explain this phenomenon.